How to improve writing skill for young learners? - Jollibekova.M. R (Zien Journals, 2022)
This article provides information on the factors to ensure the ability of young schoolchildren to write, methods of teaching correct writing, the development of essay writing skills in schoolchildren
Keywords: game; hooks; education; skill